Efektivitas Jaringan Komunikasi Kelompok Ibu – Ibu PKK Dalam Meningkatkan Partisipasi Pada Program Kelestarian Lingkungan di Kabupaten Lamongan - Arinda Septarina; Rio Kurniawan (LPPI UMN AL WASHLIYAH, 2025)
The PKK women's group plays a crucial role in implementing environmental sustainability programs. However, the success of these programs heavily relies on the communication network established among its members. This study aims to analyze the form of communication network formed within the PKK women's group in environmental sustainability programs and to identify the actors occupying central positions in the communication network, focusing on elements such as Degree Centrality, Betweenness Centrality, and Closeness Centrality. This study employs a descriptive quantitative approach involving 15 respondents who are members of the PKK women's group. Data collection techniques include questionnaires containing questions about the effectiveness of communication networks among PKK women's group members in implementing environmental sustainability programs. Additionally, the researcher collects data through observation to examine the communication patterns among members and administrators, providing insights into the dynamics within the group. The analysis technique used is Social Network Analysis (SNA) with the assistance of UCINET software.